Multicultural and Multilingual Code-Switching: A Sociolinguistic Study of PBA UIN Malang Postgraduates - Nabilah, Farah Farhatun; Aulia, Safira; Budianto, Langgeng (LPPM Universitas KH.A. Wahab Hasbullah, 2025)
This study examines the phenomenon of code-switching and code-mixing in the communication of graduate students in Arabic Language Education (PBA) at the multicultural environment of UIN Malang. The main issue addressed in this research is how code-switching and code-mixing are used in both social and academic interactions by students from diverse cultural and linguistic backgrounds. The aim of this study is to understand the impact of code-switching and code-mixing on academic communication and the social identity of students in a multicultural campus environment. The study employs a qualitative approach, with data analysis based on interviews and observations of students, as well as an analysis of conversations in WhatsApp group chats. The findings reveal that students frequently use code-switching and code-mixing to adapt to their interlocutors, facilitate communication, and enrich their vocabulary. Code-switching plays a role in strengthening the students' social identity and fostering inclusive social relationships. However, code-switching can also hinder the understanding of academic content if not used appropriately. This study concludes that code-switching and code-mixing are essential communication strategies in a multicultural academic environment, but their use must be directed and contextually appropriate.